Glucagon-like peptide-1 is associated with poor clinical outcome, lipopolysaccharide translocation and inflammation in patients undergoing cardiac surgery with cardiopulmonary bypass. (September 2020) - Nguyen, Maxime; Tavernier, Annabelle; Gautier, Thomas; Aho, Serge; Morgant, Marie Catherine; Bouhemad, Belaid; Guinot, Pierre-Grégoire; Grober, Jacques
Highlights: In patient with cardiopulmonary by-pass, GLP-1 was associated with LPS translocation. GLP-1 and LPS translocation were associated with inflammation and complications. There was no correlation between I-FABP and LPS plasma concentration. Our results support that GLP-1 could be a marker of mucosal integrity in human. Abstract: Introduction: Cardiac surgery with cardiopulmonary bypass (CPB) is associated with gut barrier dysfunction. Gut barrier dysfunction might be estimated non-invasively by lipopolysaccharide (LPS) plasma concentration. Glucagon-like peptide-1 (GLP-1) is a gut secreted hormone that is a potential marker of mucosal integrity. Our objective was to evaluate GLP-1 as a peri -operative marker of gut barrier dysfunction in patients undergoing cardiac surgery with CPB. Methods: GLP-1, intestinal fatty acid binding protein (I-FABP) and lipopolysaccharide were assayed: at induction, after CPB and 24 h after admission in the intensive care unit. The primary end-point was peri -operative lipopolysaccharide concentration (LPS concentration at those 3 time points). Results: Seventy-two patients were included in the present analysis. The highest measured post-operative GLP-1 concentration was in the sample taken 24 h after admission to intensive care, which was associated with peri -operative lipopolysaccharide plasma concentration. Patients who had the highest GLP-1 concentrations at 24 h experienced more severe inflammation and worse clinical outcomes. Conclusion: Our study supports that GLP-1 is not only a hormone of glucose metabolism but is also secreted when gut barrier is impaired in cardiac surgery with CPB. The GLP-1 levels measured 24 h after admission to the intensive care unit were associated with LPS concentration, inflammation and clinical outcomes.